REGULASI AIR SEBAGAI PERLINDUNGAN KEBUTUHAN DASAR WARGA NEGARA DALAM ERA GLOBALISASI EKONOMI - Widiyastuti, Sri (Faculty of Law, Tanjungpura University, 2018)
The era of the economy globalization is a movement that has a nationalism dimension because infinite flows of investment and capital that begin to penetrate the strategic sector economically result in fundamental problems given that this strategic sector is related to the livelihoods of the people (the basic needs of citizens) that demand protection from the state. In the field of water management that is not spared from the current globalization of the economy it has a complicated problem because the policies in the exploitation of water are considered to be contrary to the 1945 Constitution. The peak, with the issuance of Constitutional Court Decision Number 85 / PUU-XI / 2013 which decided to reject the entire contents of Law Number 7 of 2004 so that it essentially returns the exploitation of this water to the state. This writing is a conceptual legal thought that aims to find answers to the regulation of water management in Law Number 7 of 2004 concerning Water Resources contradicts the 1945 Constitution, and seeks the concept of good water regulation that can be used as a means of protection for citizens in the era of economic globalization after Law Number 7 of 2004. The results of the discussion concluded that Law Number 7 of 2004 concerning Water Resources denies the 1945 Constitution because in terms of law enforcement both ideally and normatively it has lost the constitutive elements of the enactment of a law. Meanwhile, the concept of good water regulation as an effort to protect citizens in the era of economic globalization after Law No. 7 of 2004 is regulation that adheres to the state ideology, and are able to respond to global pressures and challenges, namely with efforts to harmonize the law in the field of water.Â